ANALYSIS OF COASTLINE CHANGES USING SATELLITE IMAGERY.CASE STUDY: PESAREN BEACH, BANGKA BELITUNG ISLANDS PROVINCE - Yorizkan Anugrah, Billy
The coastline is the physical boundary between land and sea, which is not fixed because it can undergo changes due to natural processes and human activities, and one effective method to get a comprehensive and consistent picture of coastline changes over time is to use publicly available satellite imagery. This research was conducted at Pesaren Beach which is located in Pesaren, Belinyu District, Bangka Regency, Bangka Belitung Province or more precisely at the coordinates of 1°31'19.0" LS-105°50'53.8" East to 1°31'14.8" LS - 105°52'12.2 "East and aims to study and understand how to extract satellite imagery for coastlines in Indonesia, identify changes in coastlines that occur at Pesaren Beach and analyze whether marine mining has an impact on changes in coastlines at Pesaren Beach. Shoreline change detection is carried out using CoastSat, coastline detection using CoastSat is carried out by collecting satellite image data from a predetermined collection and then the image is processed to determine the coastline in the desired area. After the shoreline changes are obtained, further analysis is carried out related to shoreline changes that occur at the study site. Using CoastSat successfully obtained 1099 satellite images but only 104 images could be analyzed. This study revealed that Pesaren Beach experienced significant shoreline changes during the 3 time periods observed, namely in period 1 (1993-1998) to period 2 (2000-2009) there was a setback of 19.6 meters of coastline and then from period 2 (2000-2009) to period 3 (2013-2022) there was a setback of 8.6 meters of coastline. Then when connected to the wave climate, during the west monsoon the coastline will regress and during the east monsoon the coastline will advance and then between the west monsoon and the east monsoon there is a transitional season 1 and transition 2, the coastline during the transitional season the coastline will move according to the direction of the dominant wave. In the study location, it is estimated that the cause of shoreline retreat is offshore mining, offshore mining at this location uses the suction method which will leave marks in the form of holes that will interfere with the sedimentation process and cause erosion. However, these results are not fully valid and further studies are needed to validate the accuracy of the study results.